Blocking Liver Autophagy Accelerates Apoptosis and Mitochondrial Injury in Hepatocytes and Reduces Time to Mortality in a Murine Sepsis Model. Issue 4 (October 2018) - Oami, Takehiko; Watanabe, Eizo; Hatano, Masahiko; Teratake, Youichi; Fujimura, Lisa; Sakamoto, Akemi; Ito, Chizuru; Toshimori, Kiyotaka; Swanson, Paul E.; Oda, Shigeto
Abstract : ABSTRACT: Autophagy plays an important role in cell survival, sequestering, and degrading a wide variety of substrates. Although an increase of autophagosomes in liver has been reported in sepsis patients as well as in septic mice, the influence of autophagy on liver injury, the interaction between autophagy, and other types of cell death in sepsis remain unclear. The aim of this study was to elucidate the contribution of liver autophagy to the pathophysiology of sepsis. We performed a cecal ligation and puncture on liver-specific autophagy-deficient (Alb-Cre ERT2 /Atg5 f/f ) mice (6–8-week-old male). When compared with controls (C57BL/6), we found a significant accumulation of p62 in the liver and demonstrated a greater number of cleaved caspase-3 immunoreactive hepatocytes in these knockout (KO) mice. Additionally, we confirmed a significant increase in autophagic vacuoles in the control mice relative to KO mice; in contrast, cell shrinkage and nuclear fragmentation (morphological characteristics of apoptosis) were preferentially seen in the KO mice by transmission electron microscopy. Severe mitochondrial damage was also prominent in KO mice, relative to controls, associated with an increase of reactive oxygen species in hepatocytes. Serum aspartate transaminase levels ( P  = 0.005) and serum interleukin-6 levels ( P  = 0.020) were significantly increased in the KO mice compared with controls. Deficiency of autophagy in liver significantly decreased survival in the murine sepsis model ( P  = 0.025). In conclusion, blocking liver autophagy accelerates time to mortality in the murine sepsis model, suggesting that liver autophagy plays a protective role for organ failure through degradation of damaged mitochondria, as well as prevention of apoptosis.